2019
DOI: 10.1055/a-0871-2612
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Mobilization by Means of a Novel Orthesis in Patients after Amputation

Abstract: Introduction The mobilization of patients with diabetic foot syndrome after surgical treatment by debridement or partial amputation is usually difficult in daily practice and in inpatient care. Aim and Method A case report – with a representative case showing the innovative possibilities of an alternative mobilization option by means of a new orthesis (“iWALK 2.0®”; IWALKFree® Inc., Mansfield, Ontario, Canada) after surgical therapy of diabetic gangrene, exemplified by the successful clinical course.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Because it does not require the upper extremity during ambulation unlike crutches, routine daily activities that are either impractical or not possible using crutches are possible using the HFC. A randomized control trial with 80 patients with both upper and lower limb injuries showed that they were able to complete activities around the house using the HFC (Rambani et al, 2007) and patients had a more positive attitude to life due to the improved independence with the HFC (Barth et al, 2020). Another prior study showed that the HFC leads to less discomfort and perceived exertion compared to axillary crutches and that 90% of patients with lower limb injuries preferred the HFC over crutches (Martin et al, 2019).…”
mentioning
confidence: 99%
“…Because it does not require the upper extremity during ambulation unlike crutches, routine daily activities that are either impractical or not possible using crutches are possible using the HFC. A randomized control trial with 80 patients with both upper and lower limb injuries showed that they were able to complete activities around the house using the HFC (Rambani et al, 2007) and patients had a more positive attitude to life due to the improved independence with the HFC (Barth et al, 2020). Another prior study showed that the HFC leads to less discomfort and perceived exertion compared to axillary crutches and that 90% of patients with lower limb injuries preferred the HFC over crutches (Martin et al, 2019).…”
mentioning
confidence: 99%